PERBANDINGAN VISUAL KULIT KAMBING SAMAK NABATI PADA HASIL EKSPERIMEN METODE FOLTIK DAN METODE HYDRO DIP - Tutik Maryati; Titik Anggraini; Sri Suryanti; Swatika Juhana (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2025)
This study was conducted to compare the visual results of vegetable goat skin using the foltic method and the hydro dip method. 3 sheets of vegetable goat skin were used in this experiment. Vegetable goat skin was divided into 3 treatments. Each 1 sheet for the experiment. The first vegetable goat skin was not treated as a comparison of the initial skin. The second vegetable goat skin used the foltic method and the third goat skin used the hydro dip method. The treated vegetable goat skin was then visually compared with undyed goat skin, vegetable goat skin using the foltic method, and the hydro dip method. The color results include color clarity, beauty and uniqueness of color. The results of the method study showed that vegetable goat skin before treatment was brown, plain and plural. Vegetable goat skin in the foltic treatment produced clear, bright colors, regular and unique motifs. Furthermore, vegetable goat skin with the hydro dip method visually produced opaque, unclear, faint, abstract colors, and the water media was not measurable. Water-based dyes used in hydro dip are easily mixed with water media so that the color pigments are spread and reduced in intensity, resulting in colors that appear faded, blurry and less clear. In the foltic method, appropriate dyes and a controlled application process are usually used so that the color can penetrate and blend with the skin. Conclusion, the hydro dip method and the foltic method can be applied to vegetable goat skin